The Effect Of Peer Education On Improving Adolescent Girls' Knowledge Of Early Marriage At MA Al-Mutaqqin Suahid, Kapuas Hulu Regency - Suryani, Suryani; Afritasari, Sofia; Putri, Dwi Khalisa (Jurnal EduHealth, 2024)
Adolescence is a period of rapid growth characterized by a strong sense of curiosity, often leading to the uncritical acceptance of information in various contexts. One negative condition that can arise during this stage is adolescent sexual behavior. This study aims to determine the effect of peer education on improving adolescent girls' knowledge about early marriage at MA Al-Mutaqqin Suahid, Kapuas Hulu Regency. Method: This study employed a quasi-experimental design with a one-group pre-test and post-test approach, involving 30 respondents selected through purposive sampling. The research intervention consisted of peer education activities. Data were analyzed using univariate and bivariate methods, with the Wilcoxon test applied for statistical analysis. Results: The findings indicate a significant effect of peer education on improving adolescent girls' knowledge about early marriage at MA Al-Mutaqqin Suahid, Kapuas Hulu Regency. Conclusion: Peer education has a positive impact on increasing adolescent girls' knowledge regarding early marriage at MA Al-Mutaqqin Suahid, Kapuas Hulu Regency.